Community Responses to Contemporary Jihad Movements and Their Impact on Social Religion in Indonesia - Sukiati Sukiati; Milhan Milhan (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
Contemporary jihad movements, especially those related to Islamic extremism, have become controversial in the international community. The purpose of this study is to explore how society responds to contemporary jihadist movements, as well as what factors influence their response. This research uses a qualitative approach by collecting data through interviews with several respondents: academics, activists, and the general public. The research results show that people's responses to contemporary jihadist movements vary widely, from those who reject them to those who support them. Factors that influence people's responses include religious beliefs, life experiences, media influences, and political factors. The results of this study have important implications for the parties involved in dealing with contemporary jihadist movements. Efforts are needed to increase public education and understanding of the true teachings of Islam, as well as reduce social and political injustice, which has triggered the emergence of the contemporary jihad movement. In addition, the parties involved must also strengthen inter-religious and intercultural dialogue to create better understanding and tolerance among people. With a more comprehensive and integrated approach, it is hoped to reduce the influence and number of followers of contemporary jihadist movements and encourage the creation of better peace and security worldwide